Long Non-coding RNA MAFG-AS1 Promotes Cell Proliferation, Migration, and EMT by miR-3196/STRN4 in Drug-Resistant Cells of Liver Cancer - Chen, Tianming; Huang, Bin; Pan, Yaozhen (Frontiers in Cell and Developmental Biology, 2021)
Long noncoding RNAs (lncRNAs) have been shown to participate in the development and progression of several different types of cancer. A recent report has indicated that lncRNA MAFG‑antisense 1 (AS1) promotes colorectal cancer. However, the role of MAFG‑AS1 in hepatocellular carcinoma (HCC) remains unclear. The aim of the present study is to examine the effect of lncRNA MAFG‑AS1 in HCC. MAFG-AS1 is up-regulated in HCC cell lines. Besides, MAFG-AS1 silence suppressed cell proliferation and migration in HCC cell lines. Mechanism assays verified that miR-3196 could bind with MAFG-AS1. Moreover, miR-3196 was discovered to be lowly expressed in HCC cell lines, and its overexpression inhibited HCC cell growth and migration. Importantly, STRN4, overexpressed in HCC cell lines, was validated to be positively modulated by MAFG-AS1 through absorbing miR-3196. Moreover, knockdown of STRN4 could countervail the restraining effects of MAFG-AS1 knockdown on the growth and migration of HCC cells. LncRNA MAFG‑AS1 promoted HCC development by dampening miR‑3196 function and may thus be a novel target for treating patients with HCC.